Kecerdasan Spiritual Memitigasi Dampak Negatif Role Stress terhadap Kinerja Auditor Internal - Siti Mas'ulah; Hidayatul Khusnah; Endah Tri Wahyuningtyas (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to analyze Spiritual Intelligence Mitigating the Negative Impact of Role Stress on Internal Auditor Performance. The data used in this study are primary data distributed through online and offline questionnaires with a total sample of 35 people. The sample of this study is the internal auditor of the company registered in East Java FKSPI. Analysis tool to test hypotheses using WarpPLS 6.0 with a significance level of 0.05. The results show that the role overload negatively impacted the performance of internal auditors. Role conflict doesn't have any impact on performance. While role ambiguity positively impacts the performance of internal auditors. The moderation effect suggests that spiritual intelligence as a pure moderation is able to mitigate the negative impact of role overload and role ambiguity towards the performance of internal auditors. While spiritual intelligence as a moderation potential is incapable of mitigate the negative impact of role conflict on performance.